2016
DOI: 10.1097/igc.0000000000000598
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Recurrent Epithelial Ovarian Cancer in the Netherlands

Abstract: This population-based retrospective study showed that there might be a role for SCS in recurrent epithelial ovarian cancer especially when complete SCS can be accomplished. However, before adopting SCS as a standard treatment modality for recurrent epithelial ovarian cancer, results of 3 ongoing prospectively randomized trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
2
15
1
2
Order By: Relevance
“…1). Supporting previous findings,49 our outcome data therefore suggest that patients who have resectable platinum-sensitive recurrence should undergo surgery without further chemotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…1). Supporting previous findings,49 our outcome data therefore suggest that patients who have resectable platinum-sensitive recurrence should undergo surgery without further chemotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…In Norway, patients with first recurrence are usually referred to the gynecologic oncology department of a teaching hospital, where a multidisciplinary tumor board considers whether they should undergo SCS and PBC or PBC alone. Our study indicates that such selection led to a resection rate at SCS comparable to the results of others (13). These clinical criteria differ from those of the DESKTOP III study (10) with a positive AGO score (9).…”
Section: Discussionsupporting
confidence: 69%
“…Patients enrolled in DESKTOP III had to have complete cytoreduction after primary surgery, first recurrence at least six months after completion of primary PBC, and fewer than 500 mL ascites at recurrence. A retrospective, population-based Dutch study reported 72% complete secondary cytoreduction and a median overall survival (OS) of 51 months among these patients (13). Results from another multicenter RCT, the GOG 213 trial (11), will also be published in the near future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When preliminary promising data on the value of surgery in recurrent ovarian cancer are confirmed in prospective randomized controlled trials (DESKTOP III trial, GOG 213 trial), early detection of recurrence by means of CA125 surveillance could become important. Third, there seems to be a tendency toward performing secondary cytoreductive surgery after some courses of ''neo-adjuvant'' chemotherapy, 3 which was not allowed in the SOCceR trial. As long as there is no evidence for secondary cytoreductive surgery from randomized controlled trials, we believe that it is too early to adopt ''interval'' secondary cytoreductive surgery as a treatment option.…”
mentioning
confidence: 99%